Pengaruh Model Pembelajaran Think Talk Write Terhadap Keterampilan Menulis Teks Pidato Siswa Kelas VIII-D Smp Negeri 12 Surabaya - Visal Gusti Permana Putra; Heny Subandiyah (CV. SINAR HOWUHOWU, 2026)
This study is driven by the low speech writing skills observed among class VIII-D students at SMP Negeri 12 Surabaya, which stems from a lack of interactive learning models in the classroom. The objective of this research is to examine the effect of the Think Talk Write (TTW) model on students' speech writing skills, while concurrently evaluating teaching implementation, learning outcomes, and student responses. This pre-experimental study adopted a One Group Pretest-Posttest Design, involving a sample of 36 students during the 2025/2026 academic year. The research process began by assessing students' initial abilities through a pre-test, followed by the implementation of the Think Talk Write model as the primary intervention—during which classroom activities were directly monitored using observation sheets. The sequence then moved to a post-test to evaluate their final writing proficiency, and concluded with gathering feedback via student response questionnaires. The collected data were analyzed using descriptive and parametric inferential statistics (Paired Samples t-Test and N-Gain). The results revealed three major findings. First, the teaching process using the TTW model ran optimally with a classical implementation score of 95%, placing it in the excellent category. Second, students' speech writing skills significantly improved, as demonstrated by a t-test significance value of 0.000 < 0.05 and a substantial leap in the mean score from 42.94 to 84.17, achieving a 100% mastery rate. This improvement is further supported by a classical N-Gain score of 0.72 (high category) and an effectiveness rate of 72.21% (effective category). Third, students showed high enthusiasm during the lessons, generating a cumulative response score of 86.81%, which falls into the very good category. These combined findings demonstrate that the Think Talk Write learning model exerts a significant and effective impact on enhancing the speech writing skills of class VIII-D students at SMP Negeri 12 Surabaya.